2006
DOI: 10.1007/s11255-006-9000-1
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerotic risk factors and carotid stiffness in elderly asymptomatic HD patients

Abstract: Several studies showed that carotid atherosclerosis and stiffness are independent prognostic factors of cardiovascular morbidity and mortality in the general population and in end-stage renal disease patients. However, the impact of established risk factors on carotid structural and elastic properties in non-diabetic elderly hemodialysis patients with negative history for cardiovascular disease has not been fully elucidated. In this paper, we investigated the effect of established and potential risk factors on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 60 publications
(60 reference statements)
3
9
0
Order By: Relevance
“…These reports and our results suggest that the correlation between stiffness parameter b and plaque score may be stronger in HD patients with chronic inflammation in HD patients. Moreover, Tseke et al [26] reported that stiffening and atherosclerosis are associated with chronic inflammation as well as DBP in HD patients.…”
Section: Discussionmentioning
confidence: 99%
“…These reports and our results suggest that the correlation between stiffness parameter b and plaque score may be stronger in HD patients with chronic inflammation in HD patients. Moreover, Tseke et al [26] reported that stiffening and atherosclerosis are associated with chronic inflammation as well as DBP in HD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Secondary hyperparathyroidism is associated with a variety of complications including bone disease [63][64][65][66], uremic pruritus [67], refractory anemia [68], and cognitive and sexual dysfunction [69,70]. In patients receiving MHD, SHPT has been associated with increased cardiovascular morbidity [48, [71][72][73] and mortality [2,3]. The association of SHPT with mortality or with progression of kidney disease in CKD has not been well characterized.…”
Section: Serum Calcium Level and Calcium Intake In Ckdmentioning
confidence: 99%
“…Much emphasis has been placed on its role in the initial development of atheroma and its potential to improve risk stratification in medium-or low-risk patients [2][3][4][5] . In the carotid artery region, it has been suggested as a risk factor for the development of stroke 6) .…”
Section: Introductionmentioning
confidence: 99%